The Spatiotemporal Dynamics and Membranous Features of the Plasmodium Liver Stage Tubovesicular Network. (13th February 2014) - Grützke, Josephine; Rindte, Kerstin; Goosmann, Christian; Silvie, Olivier; Rauch, Carolin; Heuer, Dagmar; Lehmann, Maik J; Mueller, Ann‐Kristin; Brinkmann, Volker; Matuschewski, Kai; Ingmundson, Alyssa
Abstract For membrane‐bound intracellular pathogens, the surrounding vacuole is the portal of communication with the host cell. The parasitophorous vacuole (PV) harboring intrahepatocytic Plasmodium parasites satisfies the parasites' needs of nutrition and protection from host defenses to allow the rapid parasite growth that occurs during the liver stage of infection. In this study, we visualized the PV membrane (PVM) and the associated tubovesicular network (TVN) through fluorescent tagging of two PVM‐resident Plasmodium berghei proteins, UIS4 and IBIS1. This strategy revealed previously unrecognized dynamics with which these membranes extend throughout the host cell. We observed dynamic vesicles, elongated clusters of membranes and long tubules that rapidly extend and contract from the PVM in a microtubule‐dependent manner. Live microscopy, correlative light‐electron microscopy and fluorescent recovery after photobleaching enabled a detailed characterization of these membranous features, including velocities, the distribution of UIS4 and IBIS1, and the connectivity of PVM and TVN. Labeling of host cell compartments revealed association of late endosomes and lysosomes with the elongated membrane clusters. Moreover, the signature host autophagosome protein LC3 was recruited to the PVM and TVN and colocalized with UIS4. Together, our data demonstrate that the membranes surrounding intrahepatic Plasmodium are involved in active remodeling of host cells. <inline-graphic xlink:href="ark:/27927/pgg4swwqjpz" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />